An exploratory study of the LGBT community in the University of the Philippines Diliman towards creating an LGBT archive - Masilungan, Juliana Maria A.; Golfo-Barcelona, Mary Grace P. (Quezon City : School of Library and Information Studies, University of the Philippines Diliman, 2019)
In the Philippines, LGBT people are tolerated, but tent not to be accepted or understood, even within their own community. Through the west has a number of LGBT archives, the Philippines is sorely lacking in them, and because a community archive is known for emphasizing identity and empowerment, it is believed having one for LGBT Filipinos will be useful in many ways. This study thus aimed to lay the groundwork for creating an LGBT community archive within the University of the Philippines-Diliman (UP Diliman), a place with a thriving LGBT culture, by understanding the community itself Seven members of the UP Diliman LGBT community were interviewed, focusing on their identities, their understanding of the LGBT community, what they knew about collecting LGBT materials and their opinions towards archives and archiving. Results showed that the LGBT community is a constantly growing, intersectional community, and majority of the respondents believe there is a community to belong to. Most of them already collect LGBT materials, with reasons ranging from personal sentimentality to general significance to the LGBT movement. They also believe that an LGBT archive will have many uses, including - but not limited to - representation, forming community memory, preserving the LGBT heritage, having proof of history, and creating a new safe space. Overall, an archive appears to be wanted, but due to the exploratory nature of this study, more in-depth research better coverage of the community is recommended.
Thesis
Keywords: Sexual minorities -- History -- Archival resources -- Philippines; Sexual minorities -- Philippines -- Diliman